DETERMINATION OF PHENOLIC COMPOUNDS CONTENT IN PÂTÉ EXTRACT USING THE HPLC METHOD - Saidjahon Saidumarov; Barnokhon Sattarova (Western European Studies, 2025)
For the extraction of phenolic compounds, 1 g of the test sample was accurately weighed using an NV222 analytical balance (OHAUS Corporation, USA) with a precision of 0.01 g and transferred into a 50 mL conical flask. Subsequently, 25 mL of 96% ethanol was added. The chromatogram of the extract obtained from the 1 g sample was recorded, and based on the analytical results, the contents of phenolic compounds in 100 g of the sample were determined.
Keywords: pâté; reproduction; recipe formulation